Comparing adults who use cannabis medically with those who use recreationally: Results from a national sample. (October 2016) - Lin, Lewei A.; Ilgen, Mark A.; Jannausch, Mary; Bohnert, Kipling M.
Abstract: Objectives: Cannabis has been legalized for medical use in almost half of the states in the U.S. Although laws in these states make the distinction between medical and recreational use of cannabis, the prevalence of people using medical cannabis and how distinct this group is from individuals using cannabis recreationally is unknown at a national level. Methods: Data came from the 2013 National Survey on Drug Use and Health (NSDUH). All adults endorsing past year cannabis use who reported living in a state that had legalized medical cannabis were divided into recreational cannabis use only and medical cannabis use. Demographic and clinical characteristics were compared across these two groups. Results: 17% of adults who used cannabis in the past year used cannabis medically. There were no significant differences between those who used medically versus recreationally in race, education, past year depression and prevalence of cannabis use disorders. In adjusted analyses, those with medical cannabis use were more likely to have poorer health and lower levels of alcohol use disorders and non-cannabis drug use. A third of those who reported medical cannabis use endorsed daily cannabis use compared to 11% in those who reported recreational use exclusively. Conclusions: Adults who use medical and recreational cannabis shared some characteristics, but those who used medical cannabis had higher prevalence of poor health and daily cannabis use. As more states legalize cannabis for medical use, it is important to better understand similarities and differences between people who use cannabis medically and recreationally. Highlights: 17% of adults who used cannabis in the past year used cannabis medically. Compared adults who use medical cannabis with those who use recreationally. Medical cannabis users had worse health and more daily use (vs. recreational users). Important to assess for risky use in both groups